A built-in self-test approach for the embedded resistor array in TI MSP430 microcontrollers - Laprovitta, Agustín (2011)
In this paper, we propose a built-in self-test (BIST) for the resistor array in an embedded analog configurable circuit (EACC) that is present in the Texas Instruments® MSP430 microcontrollers family. The EACC is formed also by an Operational Amplifier (OA) and interconnection resources. We focus in the resistor array test due to this section establishes the feedback path for the embedded OAs and set the gain value for the EACC closed-loop configurations. The test establishes, through very simple measurements, which combinations of the resistor ladder are available for the user by using only the resources embedded in the microcontroller. The experimental results show that the BIST proposed presents a very good repeatability in the measurements with very low dispersion, for one chip, for a sample of chips and under different temperature conditions. The error in the measurements, evaluated using a higher precision voltmeter, is also low. These results show that the BIST proposed is useful for testing the functionality of the resistor array in the EACC under test using a simple strategy at a very low cost.